Teachers’ Pedagogical Practices to Support Learners’ Functional Literacy Development: The Context of Mother Tongue Language - Annette Naddumba; Logamurthie Athiemoolam (Journal of Languages and Language Teaching, 2022)
The sociocultural perspective maintains the view of understanding literacy as a social and cultural practice to describe reading and writing in multiple and evolving language activities. It means that literacy development is related to actions and beliefs which a student creates to define him or herself in particular cultural settings or circumstances. These circumstances further describe what resourceful individuals like teachers would offer or create in terms of language tasks or events to help students be identified as readers and writers. This qualitative study aimed at gaining deeper insights into teachers’ pedagogical practices to support functional literacy through mother tongue languages. Based on in-depth interviews, focus group discussions and classroom observations, this phenomenological study examined literacy instructional practices which offer a pedagogically grounded and positive learning environment where teachers use mother tongue as a medium of instruction to support learners’ early literacy acquisition processes. Thus, the study provides substantial findings which depict the role of children’s previous language experiences and teachers’ constructive classroom engagements as a basis for functional literacy development.